2017
DOI: 10.1097/id.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Ridge Dimensions of the Edentulous Mandible in Posterior Sextants

Abstract: BH decreased from mesial to distal, whereas BW showed an increase. Sex showed a significant impact on BH, with males having on average a 2.8 mm greater height than females, but not on BW. Age did not significantly influence the dimensions of the residual bone crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Our data showed that BH dimensions were higher in males than in females, while BH dimensions decreased from premolar to molars. Similarly, a significant difference in bone height between males and females has been reported in the dentulous 1 , 2 , the edentulous 7 , and both types of individual (Table 8 ) 3 5 , 8 , 9 . On the other hand, Alrahaimi et al found no significant difference between males and females regarding distances from the alveolar crest to the superior position of the mandibular canal in a study on jaws with single missing teeth 6 .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our data showed that BH dimensions were higher in males than in females, while BH dimensions decreased from premolar to molars. Similarly, a significant difference in bone height between males and females has been reported in the dentulous 1 , 2 , the edentulous 7 , and both types of individual (Table 8 ) 3 5 , 8 , 9 . On the other hand, Alrahaimi et al found no significant difference between males and females regarding distances from the alveolar crest to the superior position of the mandibular canal in a study on jaws with single missing teeth 6 .…”
Section: Discussionmentioning
confidence: 58%
“…Several authors measured bone width on different levels, from the dental crest to the edge of the alveolar canal (Table 7 ), and concurred that it increased gradually from the premolar through to the third molar region of the mandible, in both dentulous and edentulous mandibles 2 , 6 9 . Studies in edentulous subjects 6 , 7 found that BW was not influenced by sex or age. It is interesting to note that BW measurements taken at various heights in edentulous subjects were always compatible with the insertion of a standard-diameter dental implant, validating our method for calculating the C/I R. The BW in the edentulous is reportedly approximately half that of dentulous subjects, confirming the fundamental role of tooth loss in severe bone resorption.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This process reduces the horizontal and vertical dimensions of the edentulous ridge, but the buccal aspect is affected to a greater degree [ 3 , 9 , 10 ]. Consequently, a shorter and narrower ridge follows [ 11 , 12 ], and this effect contributes to a more palatal/lingual movement of the ridge [ 13 ]. Implant placement and survival may become less ideal because of these alterations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is observed in this study where the distances from MC to the buccal and lingual alveolar crests (MC-BC, MC-LC) were consistently lower in the edentulous ridge compared to the dentate ridge across all teeth regions under investigation for both Arabs and Kurds. A few studies reported similar findings ( Bressan et al, 2017a , Bressan et al, 2017b , Park, 1999 ). Differences in MC-BC and MC-LC measurements of dentate ridge in different teeth regions were also diminished when the teeth were lost which were demonstrated by almost similar measurements of the edentulous ridge of all teeth regions.…”
Section: Discussionmentioning
confidence: 61%